A estrutura de poder tradicional no stricto sensu: o caso do mestrado profissional em Administração Pública em Rede Nacional - PROFIAP - Oliveira, Fernando Porfírio Soares de (2014)
This study approaches bureaucratic organizational structures with the aim to understand the adherence procedure to virtual technologies in the stricto sensu educational administrative process. Thus, the author navigates through the formation of these organizations in Brazil with the intent to demonstrate the bureaucratic organizational culture and the consequent form of domination of those who detain power. In this epistemological construction, the author explores the culture s bureaucratic environment and the organizational power. In the analyses, it was observed the technological phenomenon in the ODL s administrative environment, which can explain the adherence procedure to structures and technological instruments for stricto sensu courses that, hypothetically, dilutes the traditional inherited organizational axiom. Therefore, it was utilized as object of study the Professional Master s degree in National Scale Public Administration PROFIAP, hence analyzing the documental content and the legislation related to institutionalization as well as the positioning of professors/coordinators and of the director of CAPES/MEC. Considering this axioms, it was concluded that the bureaucratic structures can admit ODL in the stricto sensu s environment. However, this can only be done as long as the adherence does not imply in a dilution of the traditional forms of power and institutional bureaucratic inherited dominance, as well as the alleged hegemony of the governmental structure in the educational administration adopted in person by the stricto sensu courses in Brazil